“I Think Our Writing Become Tidy, Clear and Also Perfect” Students’ Feedback on Writing Class with Technology Performance - Naria Fitriani; Zaiturrahmi Zaiturrahmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
Integrated teaching learning instruction with technology has been fascinating for EFL students currently. In writing class, it takes several times for students to revise their draft after receiving feedback. Rather than using a plain paper with bullet, students nowadays prefer screen with the keyboard. In this study, it aimed at exploring the students’ preferences on applying computer in writing class. The data from 33 university students taking Writing class were collected and analyzed descriptively. To detract bias, the teacher was also interviewed. The results revealed that 91% of the students prefer to write on email. Moreover, 88% agreed that the media is helpful to ease the writing and revise English paragraph. However, teacher assumed that several students do not know how to use computer correctly.